(untitled) (TAJ: Journal of Teachers Association, 2020)
Introduction: Fiberoptic bronchoscopy is a very important tool in the modern era in the field of pulmonary medicine in arriving to a definite diagnosis. Since the introduction of the first flexible fiberoptic bronchoscope (FOB) has been a valuable tool in the diagnosis of pulmonary diseases. Material & methods: This study was conducted in Rajshahi Medical College Hospital (RMCH), Rajshahi. It was undertaken to study the role of fiberoptic bronchoscopy (FOB) in diagnosis of pulmonary disease. The study period was between 1st June 2017 to 30th June 2019. A total number of 300 patients (48 females and 252 males) who underwent elective fiberoptic bronchoscopy were included in this study. Data was collected from hospital record regarding age, clinical presentation, diagnostic procedure and outcome. Results: A total number of 300 patients had fiberoptic bronchoscopy during the study period. 252(84.00%) patients were male and 48(16.00%) were female. As per age distribution 8(2.67%) were of age group 20-32 years and majority 111(37.00%) of patients were in age group 60-72 years. Min age group was 20 and max 85 and the mean±SD age was (58.70±13.11). Occupation of the study participants most of them are farmer 134(44.67%). Bronchoscopy findings: most of the patients had malignant lesion 228(76.00) and a few had foreign body 6(2.00%), mean±SD (2.03±0.68). Majority of the patients had problems in their upper lobe 167(55.67%) and some of the patients had problems in lower lobe 22(7.33%), mean±SD (0.97±0.15). Regarding location, left principal bronchus were involved in 115(38.33%), upper lobe 95(31.67%), lower lobe 36(12.00%) and lingular lobe 36(12.00%), mean±SD (2.01±1.02). Trachea was found normal 261(87.00%) and growth 29(13.00%), mean±SD (1.13±0.33). Vocal cord found normal 246(82.00%) and palsy was found in 54(18.00%), mean±SD (1.18±0.38). carina findings were normal 54(18.00%), blunt 230(76.67%) and sharp 13(4.33%), mean±SD (1.26±0.50). Conclusion: FOB can be successfully employed for the diagnosis of lung diseases, including malignancies and granulomatous lesions. Routine bronchoscopy technique continues to have a good diagnostic yield in current clinical practice in various lung diseases. TAJ 2020; 33(2): 46-55